Monitoring of geo-economic transformation of the world market of tourist services - Pavel Shukanov; Alexander Goryachоv; Victor Karpenko; Nina Karpenko (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
In the article on the basis of system-synergetic approach propose theoretical and methodological background of the publicly-geographical monitoring of global transformation of world market of tourist services. Among the new methods used in research are methods of foresight technologies and socio-economic modeling of the development of the object. Proposed and justified from the standpoint of socio-economic geography concept of «global market space» as functional and organizational environment and form of interaction between the cultural and trade and economic fields in the process of transformation of national economies.